Kontribusi Usaha Ternak Sapi Potong terhadap Pendapatan Petani di Kecamatan Jumantono Kabupaten Karanganyar - Junianto Tri Prakosa; Bambang Sarosa (Universitas Sebelas Maret, 2003)
The aim of this research is to analyze the income amount of from the agriculture business of beef cattle, to analyze the income contribution of beef cattle business toward the farmer income and exploring the efficiency of beef cattle business.The research basic method is using the analysis descriptive method. The selection of research area conduct purposively that is in Karanganyar regency because of its potentiality for the development of beef and the ability of the natural condition to support the business. This business also improves beef population amount for many years and develops the beef quality toward the improvement of local beef. After that, the sampling area is intentionally chosen in the basic of the largest amount of the beef, and the place is Jumantono. For the sampling farmer it is used proportional random sampling. The number of respondent is 40 people consist of 22 people from Genengan village and 18 people from Sringin village. The data which is gathered consist of primary and secondary data using the questioner, observation, and notation. The research is needed a year observation from September of 2001 to August of 2002 during the running of the beef cattle business.The research results show that the average ofbeef property is 1,6 beef/cattle business. The average income of this business is Rp. 2.428.750,00/cattle business/year or Rp. 349.316,41/beef/year. It can be concluded that the income Rp.1.496.093,75/cattle business/year or Rp. 935.058/beef/year. Meanwhile, the average contribution of this business toward the farmer income is 33,6%. The beef cattle business efficiency (R/C ratio) is 2,6, it shows that this business is beneficial. The efficiency can only be achieved by better and advance maintenance and also considering the feed composition, health, and breeding of the beef by using the artificial insemination.